The SmartAG Partner: CCAFS East Africa Quarterly Newsletter, January - March 2014 - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
We bring you news on policy, science and from the field (CCAFS Climate Smart Villages) on climate change and food security matters from East Africa. In the run up the World Economic Forum, CNBC Africa sought our views regarding food security in Africa. Read more about what Africa needs to move forward in this area. Under the same section, find out how African countries are moving forward with regard to transforming agriculture in a changing climate despite slow progress at the UNFCCC driven talks. Climate Analogues and Scenarios enable farmers and other stakeholders to have a glimpse of past, present and future climates. Under our science updates section, find out why this approach is useful for designing appropriate adaptation strategies in agriculture. We also introduce you to the CCAFS Big Facts site that has been re-launched. This is a useful resource for latest facts and data on Agriculture, Climate Change and Food Security. From a recent study, read how smallholder agricultural systems in Kenyan highlands might intensify and or diversify their production in the future under a range of different scenarios. Our researchers linked various socio – economic scenarios with regional and household models to identify these changes. In the last section, field updates, read about climate information services for farmers in Nyando, Western Kenya and how this impacts decision making. Elsewhere, in Lushoto, Tanzania, find out how adoption of improved bean varieties and better agronomic practices, led to a threefold increase in bean yields compared to local varieties